Family-owned and non family-owned SMEs: empirical evidence of survival determinants - Nunes, Paulo (2015)
Using probit regressions and on the basis of two research samples: 1589 family-owned SMEs and 485 non family-owned SMEs, this paper analyzes if there are significant differences between family-owned SMEs and non family-owned SMEs for determinants of survival. The empirical evidence obtained shows the existence of significant differences between these two types of firms for the determinants of survival. In the context of family-owned SMEs, the empirical evidence obtained allows us to conclude that: size, age and R&D expenditure are neither positive nor restrictive determinants of survival; cash flow and labour productivity are positive determinants of survival; and, debt, interest paid and risk are restrictive determinants of survival. In the case of non family-owned SMEs, size, age, cash flow, debt and R&D expenditure are positive determinants of survival, with interest paid, risk and labour productivity being neither positive nor restrictive determinants of survival.